The anti-aging properties of a human placental hydrolysate combined with dieckol isolated from Ecklonia cava. Issue 1 (December 2015) - Jang, Su; Lee, Do; Kim, Seung; Kim, Gwang; Park, Da; Park, Jung; Han, Daehee; Choi, Jae; Lee, Yoon-bok; Han, Nam-Soo; Kim, Yun; Han, Jeongsu; et al.
Abstract Backgrounds In the present study, we aimed to examine the anti-aging properties of human placental hydrolysate (HPE) and dieckol (DE) fromEcklonia cava against free radical scavenging, muscle hypertrophy-related follistatin mRNA expression, amelioration of cognition-related genes and proteins, inhibition of collagenase-regulating genes, and elastinase activity. Methods The anti-aging effects were examined in human fibroblast (CCD986sk), mouse myoblast (C2C12), and neuroblastoma (N2a) cell models, by employing various assays such as 2, 2-diphenyl-1-picrylhydrazyl hydrate (DPPH) scavenging, hydroxyl radical-mediated oxidation, quantitative real-time polymerase chain reaction, enzyme activity, and immunocytochemistry observation. Results Our results show that HPE combined with DE (HPE:DE) strongly scavenged DPPH radicals and protected proteins against degradation by hydroxyl radical attack. HPE:DE effectively inhibited matrix metalloproteinase-1 expression, protein kinase C alpha expression, and elastinase activity. Furthermore, HPE:DE improved the expression of cognition-related genes (choline acetyltransferase and vesicular acetylcholine transporter). These events may proactively contribute to retard the aging processes and the abrupt physiological changes probably induced by mitochondrial dysfunction with aging. Conclusions Based on these findings, we conclude that the combined treatment of HPE:DE may be useful for anti-aging therapy in which the accumulation of oxidative damage is the main driving force.